Catalysis of DNA cleavage and nucleoside triphosphate synthesis by NM23-H2/NDP kinase share an active site that implies a DNA repair function - Postel, Edith H. (The National Academy of Sciences, 2000)
NM23/NDP kinases play an important role in development and cancer but their biological function is unknown, despite an intriguing collection of biochemical properties including nucleoside-diphosphate kinase (NDP kinase), DNA binding and transcription, a mutator function, and cleavage of unusually structured DNA by means of a covalent enzyme–DNA complex. To assess the role of the nuclease in human NM23-H2, we sought to identify the amino acid responsible for covalent catalysis. By sequencing a DNA-linked peptide and by site-directed mutagenesis, we identified lysine-12, a phylogenetically conserved residue, as the amino acid forming the covalent complex with DNA. In particular, the ɛ-amino group acts as the critical nucleophile, because substitution with glutamine but not arginine completely abrogated covalent adduct formation and DNA cleavage, whereas the DNA-binding properties remained intact. These findings and chemical modification data suggest that phosphodiester-bond cleavage occurs by a DNA glycosylase/lyase-like mechanism known as the signature of base excision DNA repair nucleases. Involvement of NM23/NDP kinase in a DNA repair pathway would be consistent with its role in normal and tumor cell development. Additionally, lysine-12, which is known in the x-ray crystallographic structure to lie in the catalytic pocket involved in the NDP kinase phosphorylation reaction, was found essential also for the NDP kinase activity of NM23-H2, suggesting that the two catalytic activities of NM23-H2 are fundamentally connected.